Bacterial Over-Growth Syndrome (BOGS) and its Therapeutic Management in a Labrador dog – A Case Report - Swethasri P.T.; S.C.Halmandge; S.P. Sarangamath; Panchasheel; M. Mounika (The Indian Veterinary Journal, 2026)
A two-year-old female Labrador was presented with a complaint of severe itching and offensive odour for the past two weeks. Clinical examination revealed significant paronychia, hyperpigmented axillae and erythema on the ventral abdomen. Skin scraping examination was performed for mite identification and microbial culture and isolation. Gram staining of the culture revealed heavy colonization of the cocci species. Therapeutic management was done with a combination of topical, systemic and supportive therapy for three weeks. The dog showed no recurrence of the condition post- treatment.